Potensi Senyawa Antioksidan Yang Terkandung Dalam Kayu Secang (Caesalpinia sappan) Untuk Perawatan Kulit Alami - Ulinnuha Nur Faizah; Nida Ni’matul Maula; Rifqi Anjar Mustika; Sri Wahyuni (Institut Agama Islam Negeri Kerinci, 2023)
Secang tree (Caesalpinia sappan L.) is generally used for traditional medicine to treat various diseases. Secang contains phenolic compounds such as gallic acid, brazilin and brazilein. As it is known that this phenolic compound has a very high antioxidant content. People generally use the sappan plant (Caesalpinia sappan L.) as herbal medicine, especially the wood part. The antioxidants contained in secang wood (Caesalpinia sappan L.) can be used to prevent premature aging of the skin and prevent free radicals. Compared to using chemicals, natural materials can produce sludge which is more easily degraded and minimizes side effects. As a result, sappan has the potential as a medicinal herbal drink, especially for skin health. The purpose of this study was to determine the potential of antioxidant compounds in sappan wood (Caesalpinia sappan L.) which can be an alternative natural skin care. The method used is a literature study. The results showed that the potential antioxidant compounds contained in secang wood (Caesalpinia sappan L.) can be used as an alternative to natural skin care, namely preventing free radicals, treating acne, preventing premature aging, brightening the skin, and preventing the growth of cancer cells in the skin.